1994
DOI: 10.1183/09031936.94.07091610
|View full text |Cite
|
Sign up to set email alerts
|

Beta 3-adrenoceptor agonists, BRL 37344 and SR 58611A, do not induce relaxation of human, sheep and guinea-pig airway smooth muscle in vitro

Abstract: The existence of atypical-or β 3 -adrenoceptors has now been generally accepted. These receptors have been shown to be abundant in adipose tissue and in a number of gastrointestinal smooth muscle preparations. A recent study reported that β 3 -adrenoceptor stimulation mediated relaxation of isolated canine bronchial smooth muscle. The aim of the present study was to extend this observation to other species.We investigated the in vitro responses of guinea-pig, human and sheep bronchial smooth muscle to isoprena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
0
32
1
Order By: Relevance
“…The relaxant effect of different extracts from Thymus vulgaris on tracheal chains of guinea pigs might be due to several different mechanisms including stimulation of β-adrenergic receptors, inhibition of histamine H 1 receptors or an anticholinergic property of this plant, because the relaxant effect of β 2 -stimulatory (Martin et al, 1994;Linden et al, 1993), histamine H 1 receptor inhibitory (Popa et al, 1984) and anticholinergic drugs (Loenders et al, 1992) have been shown in previous studies. To evaluate the contribution of β-adrenergic stimulatory and/or the H 1 histamine blocking effect of macerated and aqueous extracts from this plant on their bronchodilatory effects, the effects of these extracts on tracheal chains with inhibited β-adrenergic and histamine H 1 receptors by propranolol and chlorphenamine respectively, were re-examined in group 3 experiments.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The relaxant effect of different extracts from Thymus vulgaris on tracheal chains of guinea pigs might be due to several different mechanisms including stimulation of β-adrenergic receptors, inhibition of histamine H 1 receptors or an anticholinergic property of this plant, because the relaxant effect of β 2 -stimulatory (Martin et al, 1994;Linden et al, 1993), histamine H 1 receptor inhibitory (Popa et al, 1984) and anticholinergic drugs (Loenders et al, 1992) have been shown in previous studies. To evaluate the contribution of β-adrenergic stimulatory and/or the H 1 histamine blocking effect of macerated and aqueous extracts from this plant on their bronchodilatory effects, the effects of these extracts on tracheal chains with inhibited β-adrenergic and histamine H 1 receptors by propranolol and chlorphenamine respectively, were re-examined in group 3 experiments.…”
Section: Discussionmentioning
confidence: 90%
“…A decrease in tone was considered as a relaxant (bronchodilatory) effect and expressed as a positive percentage change in proportion to the maximum contraction and an increase in tone was considered as a contractile (bronchoconstrictory) effect, which was expressed as a negative percentage change (Martin et al, 1994).…”
Section: Protocolsmentioning
confidence: 99%
“…This finding may have significance for epithelial cell function, where functional b 3 -adrenoceptor has been described, but not for ASM, which seemingly lacks expression of this subtype [32][33][34]. In addition to being widely expressed on ASM [31], b 2 -adrenoceptors are also expressed on The free a subunit then augments the basal activity of one or more isoforms of adenylyl cyclase (AC), resulting in an increase in the formation of cAMP from adenosine triphosphate (ATP).…”
Section: Adrenoceptors In the Lungmentioning
confidence: 91%
“…Similar result was observed with atropine. These indicate that ELEGS has a nonspecific spasmolytic activity on smooth muscles that may probably be due to β-adrenergic stimulatory (Martin et al, 1994), histamine H1 (Popa et al, 1984) and/or muscarinic inhibition (Linden et al, 1993). However, result obtained from rabbit jejunum after addition of ELEGS up to 6.4 mg/ml to baths pretreated with propranolol was not significantly different from the control.…”
Section: Elegs (Mg/ml)mentioning
confidence: 99%